Investigating The Effect Of Grammatical Differences Between English (L2) And Arabic (L1) On Saudi Female Students’ Writing Of English - Fatima Salamh Albalawi (European Scientific Journal, ESJ, 2016)
The purpose of this study is to investigate whether the grammatical errors committed by the Female Saudi Students can be attributed to their mother tongue interference. This study analyses 120 English essays written by Arabic speaking Saudi Female Students studying at Prince Fahad Bin Sultan University. Since the researcher’s mother-tongue is also Arabic, the interference of Arabic language committed by these students was easily found upon examining their writings. The findings of this study revealed that the transfer of Arabic linguistic structures influenced the English writings of Saudi Female Students on the grammatical level. Furthermore, the English writing skill of the Saudi Female Students needs development. The study concluded that the percentage of the total grammatical errors committed by the Saudi students was 1179 errors. Out of the 1179 errors, 59 errors were in Active and Passive Voice, 118 errors in plurality, 118 errors also in articles, 165 errors in the use of word order, 188 errors in prepositions, 244 errors in Verb Tenses and Form, and 306 errors in Subject-verb agreement which is the highest percentage of errors as a result of the effect of the L1. On the basis of these findings, a group of recommendations and some pedagogical implications for educators and policy makers were provided to improve the EFL teaching-learning process.